Dialogue sur le mariage, dialogue dans le mariage. Sur le troisième livre de la Civil Conversatione de Stefano Guazzo - Dimke-Kamola, Joanna (Studia Romanica Posnaniensia, 2015)
The starting point for this study of the marriage according to Guazzo is the notion of conversation in its original meaning, as living together. The treaty of Guazzo (1574) develops the concept of « civil conversazione » in which men exchange their opinions, but especially support each other and show mutual respect and amiability, which avoids conflicts. The study shows the analogies between such ideal of communication and Guazzo’s vision of the marriage – both envisaged in the humanistic and Christian perspectives: as foundations of society and means of mutual edification. Guazzo’s discourse concerning conversation of the spouses oscillates between the necessity of accomodation to the spouse (related to concealment) and sincerity. Given the complexity of codes that characterize other types of communication, « marital conversazione » is presented as the closest to the ideal of transparency.